A reactive nitrile-rich phosphonium polyelectrolyte derived from toxic PH3 tail gas: Synthesis, post-polymerization modifications, and unexpected LCST behaviour in DMF solution. (1st March 2022) - Hong, Yu-Lin; Sun, Jian; Yang, Hong-Wei; Wang, Chang; Liu, Yun; Tan, Zhi-Wei; Liu, Cheng-Mei
Abstract: Nitrile-rich polymers have found applications in carbon fibre, functional materials and rubber industry, though nitrile-rich polyelectrolytes have seldom been reported before. Here we present a nitrile-rich reactive phosphonium-based polyelectrolyte (PVBzTCPC) synthesized by the RAFT polymerization of 4-vinylbenzyl-tris(2-cyanoethyl)phosphonium chloride (VBzTCPC), a CN-rich phosphonium monomer prepared from tris(2-cyanoethyl)phosphine (TCP) and 4-vinylbenzyl chloride. The RAFT polymerization behaviour of the monomer was studied and it was found that the polymerization of monomer proceeded in a controlled/living manner. PVBzTCPC underwent the Wittig reaction and vinyl groups were introduced into the polymer chain as polymerizable pendant groups. Post-polymerization modifications of PVBzTCPC through the nitrile group proceeded successfully and the modified polymers were also phosphonium-based polyelectrolytes. PVBzTCPC showed a high tendency to form an undissolved polyelectrolyte complex with sodium perfluorooctanoate in aqueous solution, which provided a possible way of removing this persistent organic pollutant from water. The DMF solution of CN-rich PVBzTCPC showed LCST-type (lower critical solution temperature) phase transition without adding any foreign salts over 100 °C, and a possible mechanism of LCST transition was proposed. Graphical abstract: Image 1 Highlights: A well-defined, CN-rich phosphonium polyelectrolyte was prepared from PH3 tail gas via RAFT polymerization. The polyelectrolyte possesses numerous post-polymerization modification possibilities. The polyelectrolyte shows LCST-type phase transition in DMF solution without any additives.